ANALISIS PENGARUH IKLAN, VARIAN DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN ROTI BROWNIES PADA TOKO AMANDA BROWNIES DI BOYOLALI - Khumairoh, Sindy; Rahayu, Listyowati Puji; Safitri, Unna Ria; Hegy Suryana, Alean Kistiani; Sri Anggorowati, Luki (Universitas Boyolali, 2024)
This study aims to determine whether Instagram social media ads, product variants and service quality affect purchasing decisions at Amanda Brownies Boyolali branch. The population in this study was consumers who were Amanda Brownies Boyolali branch. Data collection techniques through the distribution of questionnaires with a sample of 97 respondents. The research method used is quantitative method. Testing of data instruments is carried out with validity tests and reality tests, for data analysis used normality tests, multicollinearity tests, heterokedasticity tests, and hypothesis tests to find out whether the variables have a significant relationship. The results of the study partially show that the advertising variable with the value of sig. 0.822 > 0.05 which means insignificant. While the variable product variant with sig value. 0.071 > 0.05 which means insignificant and quality of service with S value. 0.000 < 0.05 which means significant. The results of the study with the calculation of the F-test obtained the sig value. (0.000) < 0.05 which means that advertising variables, product variants and service quality simultaneously influence purchasing decision variables. Based on the calculation of the Adjusted Rsquare value, it shows that advertising variables, product variants and service quality together are able to explain service decision variables with a value of 0.504 or 50.4%.